Neuroprotective and anti-inflammatory effect of pectolinarigenin, a flavonoid from Amazonian Aegiphila integrifolia (Jacq.), against lipopolysaccharide-induced inflammation in astrocytes via NFκB and MAPK pathways. (November 2021) - Heimfarth, Luana; Nascimento, Leandro da Silva; Amazonas da Silva, Márcia de Jesus; Lucca Junior, Waldecy de; Lima, Emerson Silva; Quintans-Junior, Lucindo José; Veiga-Junior, Valdir Florêncio da
Abstract: Neurodegenerative diseases affect millions of people worldwide. Regardless of the underlying cause, neuroinflammation is the greatest risk factor for developing any of these disorders. Pectolinarigenin (PNG) is an active flavonoid with several biological properties, anti-metastatic and anti-inflammatory activity. This study investigate the biological effects of PNG in macrophage and astrocyte cultures, with focus on elucidating the molecular mechanisms involved in the PNG activity. J774A.1 murine macrophage or cerebral cortex primary astrocytes primary cultures were treated with different concentration of PNG (1–160 μM) and the inflammatory process was stimulated by LPS (1 μg/ml) and the effect of PNG in different inflammatory markers were determined. PNG did not affect astrocyte or macrophage viability. Moreover, this flavonoid reduced NO release in macrophages, attenuated astrocyte activation by preventing the overexpression of glial fibrillary acidic protein, and decreased the release of inflammatory mediators, IL-1β and IL-6 induced by LPS by the glial cell, as well as enhanced basal levels of IL-10. In addition, PNG suppressed NFκB, p38MAPK and ERK1/2 phosphorylation in astrocytes culture induced by LPS. The results show clear evidence that this novel flavonoid protects astrocytes against LPS-induced inflammatory toxicity. In conclusion, PNG presents neuroprotective and anti-inflammatory property through the inhibition of inflammatory signaling pathways. Graphical abstract: Image 1 Highlights: Pectolinarigenin (PNG) presents neuroprotective and anti-inflammatory property. PNG inhibit IL-6 and IL-1β production induced by LPS. PNG stimulate IL-10 release. PNG block NFκB and MAPK activation induced by LPS. PNG (1–30 μM) does not reduce astrocytes or macrophages viability.